2016
DOI: 10.5127/jep.045414
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fear Domain Match and Baseline Bias in Interpretation Training for Contamination Fear

Abstract: Cognitive Bias Modification for anxious interpretations (CBM-I) is a computerized training program designed to reduce threatening interpretations of ambiguous information. In addition to testing the efficacy of CBM-I for contamination fear on various cognitive outcomes and emotional vulnerability, the current study examined whether the content of CBM-I must match a person's fear domain to be efficacious, and examined the moderating role of preexisting interpretation bias on CBM-I's efficacy. Participants (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…As predicted, our positive training led to a greater increase in adaptive interpretive bias towards ambiguous contamination-related situations whereas the neutral training did not. This finding converges with those reported by Beadel et al (2016) and Conley and Wu (2018), who were also able to train an adaptive bias in individuals with contamination concerns, despite using either a different set of training items or CBM-I methodology. Importantly, like Conley and Wu (2018), we showed that our positive training, relative to neutral training, was associated with less avoidance of contaminants on our behavioural approach tasks.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…As predicted, our positive training led to a greater increase in adaptive interpretive bias towards ambiguous contamination-related situations whereas the neutral training did not. This finding converges with those reported by Beadel et al (2016) and Conley and Wu (2018), who were also able to train an adaptive bias in individuals with contamination concerns, despite using either a different set of training items or CBM-I methodology. Importantly, like Conley and Wu (2018), we showed that our positive training, relative to neutral training, was associated with less avoidance of contaminants on our behavioural approach tasks.…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, like Conley and Wu (2018), we showed that our positive training, relative to neutral training, was associated with less avoidance of contaminants on our behavioural approach tasks. Our results showing the cognitive changes due to CBM-I also echoes Beadel et al (2016), such that our positive training led to a reduction in contamination-related cognitions as measured by the Contamination Cognitions Scale (Deacon & Olatunji, 2007). These findings appear promising for the clinical utility of CBM-I in individuals with contamination concerns.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations